Understanding variations in diarrhea management across healthcare facilities in Bangladesh: a formative qualitative study - Nour Elshabassi; Stephanie C Garbern; Rochelle K Rosen; Monique Gainey; Sabiha Nasrin; Nur H Alam; Sufia Sultana; Tahmida Hasnin; Adam C Levine (Journal of Infection in Developing Countries)
Introduction: Acute diarrhea remains a leading cause of morbidity and mortality with over 6.3 billion cases and 1.3 million deaths annually. Despite the existence of standardized guidelines for diarrhea management, wide variability in clinical practice exists, particularly in resource-limited settings. The goal of this study was to qualitatively explore how diarrhea management in Bangladesh varies according to resource availability, clinical setting, and provider roles.